सर्व प्रश्नांची उत्तरे पाठवा
प्लीज
Attachments:
![](https://hi-static.z-dn.net/files/dd6/49fdd255179d4667541d6250ab0e7914.jpg)
Answers
Answered by
4
Explanation:
Given, f(x)=−∣x−2∣−3
We know that modulus is always greater than or equal to zero, so we have ∣x−2∣≥0 , which implies −∣x−2∣≤0.
Therefore −∣x−2∣−3≤−3 , which implies y≤−3
Similar questions
Computer Science,
1 month ago
Science,
1 month ago
English,
3 months ago
Business Studies,
3 months ago
English,
11 months ago
Accountancy,
11 months ago
Math,
11 months ago